Prediction of Age Loss on 160 KVA Transformer PT. PLN ULP Kenjeran Surabaya using The Linear Regression Method - Widagdo, Reza Sarwo; Andriawan, Aris Heri (PROGRAM STUDI TEKNIK ELEKTRO, 2023)
Distribution transformer is one of the important equipment in the distribution of electricity to consumers. The electricity demand increases every year, so that the transformer works optimally, it must also be considered regarding the loading. According to IEC 354 if the transformer is loaded stable 80% with conditions around 20℃ and the winding temperature is 98℃, but if the ambient temperature is more than 20℃ then the age of the transformer will decrease. With an average loading of 71.75%, based on the calculation that the predicted useful age of the 160 KVA distribution transformer in 2027 will have an age loss index of 1.1 p.u, so it is estimated that the remaining age of the distribution transformer is 12 years and 7 months. Analysis using a statistical approach assisted by SPSS software was also carried out to see how much influence the loading has on the age loss of the transformer.